MULTICULTURALISM, ISLAM AND ETHNIC’S DIVERSITY: THE CASE IN INDONESIA - Razak, Yusron (Lintas Cendekia Publishing, 2023)
This article examines the Islamic concepts of multiculturalism in connection with the fact that humans are created coming from various religious and cultural backgrounds. By taking the Indonesian context as the case study, the author explores how any attempts at implementing the multicultural values in the societies face obstacles and difficulties due to the high number of religious conflicts that occurred in many parts of the country. The author nevertheless presents some evidence that the Islamic propagation concepts developed by the main Indonesian Muslim organisations, that is Nahdhatul Ulama and Muhammadiyah, can be used as the basis for the strengthening of multiculturalism in the Indonesian public sphere. In this article, the authors argues that the achievement of the Indonesian founding fathers in uniting hundreds of ethnic groups into one nation cannot be separated from Islamic beliefs they adhere to that promote moderate and inclusive values.